2020
DOI: 10.3390/ma14010060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Deformation Behavior of Copper Nickel Alloys under Sliding

Abstract: The microstructural evolution in the near-surface regions of a dry sliding interface has considerable influence on its tribological behavior and is driven mainly by mechanical energy and heat. In this work, we use large-scale molecular dynamics simulations to study the effect of temperature on the deformation response of FCC CuNi alloys of several compositions under various normal pressures. The microstructural evolution below the surface, marked by mechanisms spanning grain refinement, grain coarsening, twinn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 58 publications
(76 reference statements)
0
11
0
Order By: Relevance
“…The methodology presented in this article can also be used to study phenomena linked to near-surface microstructural evolution in the context of nano-indentation, such as [ 73 , 74 ]. In addition, the research sheds lights on the surface evolution during tribological loading [ 75 ] and reveals the significant contribution of dislocation activities near the contact surface [ 76 , 77 ] to the microstructure evolution.…”
Section: Discussionmentioning
confidence: 99%
“…The methodology presented in this article can also be used to study phenomena linked to near-surface microstructural evolution in the context of nano-indentation, such as [ 73 , 74 ]. In addition, the research sheds lights on the surface evolution during tribological loading [ 75 ] and reveals the significant contribution of dislocation activities near the contact surface [ 76 , 77 ] to the microstructure evolution.…”
Section: Discussionmentioning
confidence: 99%
“…The time step was set to 2 fs, and a Langevin thermostat with a coupling time of 3.5 ps was applied in y direction to keep the temperature of the substrate at the desired value while reproducing a realistic heat conductivity of ferrous work pieces [46]. In order to obtain data for a range of temperatures that might occur directly at the interface between abrasive grain and work piece during the grinding process, we performed simulations at 300, 600, and 900 K, as maintaining the correct heat conductivity with a work piece thickness of 40 nm does not allow the surface to heat up by more than approximately 100 K [47]. The lowest 3 Å of the work piece were kept rigid to avoid torque on the work piece during grinding.…”
Section: Modeling Detailsmentioning
confidence: 99%
“…[12], to address the origin of friction at the nano-scale and its links to what is perceived at larger time and length scales. Recent MD studies have revealed the deformation mechanisms responsible for surface and subsurface permanent deformation and microstructural changes in binary alloys, also exploring the temperature effect under dry sliding [13][14][15][16] at the atomic scale. Though the MD simulation results would be able to provide the meso-scale simulation with more fundamental information (e.g.…”
Section: Introductionmentioning
confidence: 99%